Getting interested: Developing a sustainable source of motivation to learn a new language at school. (November 2019) - Fryer, Luke K.
Abstract: This review positions current conceptions of interest and its development as a critical and (importantly) sustainable source of motivation for learning a new language across formal education. We begin with the gap in our understanding of motivation to learn a new language generated by the longstanding dominance of applied linguistics identity/socio-cultural theoretical frameworks in school learning environments. The Four-Phase Model (Hidi & Renninger, 2006), and an extension with specific relevance for the highly structured nature of formal education, is reviewed and implications for second and foreign language learning classrooms are drawn. This review concludes with future directions for interested language learning researchers and essential first steps for instructors seeking to support the initiation and continued development of students' interest in their languagelearning classrooms.